The characteristics of government internal auditor in supporting good governance (A case study in Dompu District Inspectorate) - Fauzi Rahman; Rr. Titiek Herwanti; Rr. Sri Pancawati M (Universitas Hayam Wuruk Perbanas, 2016)
Regulation of Ministry of State Apparatus Empowerment (Permenpan) Number PER/05/M.PAN/03/2008, on the auditing standards of APIP (Government Internal Auditor), regulates the characteristics of APIP. The adequate characteristics of APIP are expected to support the realization of good governance. However, many problems related to the characteristics of APIP of Dompu District Inspectorate still occur, con-sisting of its expertise, independence, and objectivity. All of these problems are sus-pected to have caused agency problems in local government. This research was con-ducted using phenomenological qualitative method with a case study approach. This study used participatory observation, in-depth interview, and documentation for anal-ysis. The research found as the following: 1) the existence of agency problem caused by the conflict of interests between local government and APIP; 2) the lack of APIP’s mastery of accounting standards and; 3) the lack of APIP’s knowledge of law, account-ing, engineering, public administration, agriculture, statistics, and state administra-tion. In addition, the problems of independence and objectivity are still often found in the characteristics of APIP of Dompu District Inspectorate when auditing. Overall, the inadequate characteristics of APIP have been unable to improve participation, accountability related to financial statement quality, rule of law, and transparency of Dompu District Government.